Polymorphisms detected in the tyrosinase and matp (slc45a2) genes did not explain coat colour dilution in a sample of Alpaca (Vicugna pacos) - Cransberg, R.; Munyard, Kylie (Elsevier BV, 2011)
The molecular basis of the inheritance of alpaca fibre colour is poorly understood. It is likely that colour dilution is having an influence on alpaca fibre colour, with all primarily pheomelanic animals differing mainly in their total melanin concentration, as opposed to relative concentrations of pheomelanin and eumelanin. Candidate genes to cause such dilution include tyrosinase (tyr) and membrane associated transport protein (matp), both of which have been associated with coat colour dilution in other species. PCR primers were designed in regions surrounding each exon of tyr and matp and these exons were sequenced in 24 animals with dilute or non-dilute colour phenotypes from around Australia. No polymorphism found in the coding region of any tyr or matp exon was associated with dilution in fibre colour.